ALL BARK NO BITE? An explorative case study of BrewDog's Corporate Political Advocacy campaign - Dinér,Olivia; Sävman,Alice (2023)
In times of political divisiveness, Corporate Political Advocacy (CPA) has emerged as a commonly used communication strategy whereby brands voice support for socio-political issues. Despite its increasing prominence, research of CPA in the field of strategic communication is scarce. Therefore, this qualitative study examines BrewDog, a company inclined to engage in conversations that hold strategic significance, demonstrating a long history of CPA. Renowned as a challenger brand, BrewDog embodies a distinct culture of punk ethos fostered by its entrepreneurial leaders. Given these characteristics, it was no surprise when the company marked its opposition to Qatar and FIFA by launching the Anti-sponsor of the World F*Cup campaign. The political stance triggered a significant backlash against BrewDog; despite this, the brand managed to gain market shares. This contradictory outcome motivated the research objectives of analysing along which dimensions BrewDog was criticised and how the brand strategically communicated to counter the backlash. Through a qualitative content analysis and inductive coding, five dimensions of criticism spawned from the analysis: Motives, Congruence, Practices, Independence and Sacrifice. These represent crucial aspects for achieving authentic CPA and are summarised in the proposed theoretical framework MCPIS, serving as a guiding tool for companies engaging in CPA. Finally, the study concludes that BrewDog’s entrepreneurial leadership and punk ethos mitigated the negative effects of the backlash.
Keywords: Corporate Political Advocacy; Authenticity; Woke-washing; Entrepreneurial Leadership; CEO Activism; Challenger Brand; BrewDog